EURADOS work on internal dosimetry. (October 2018) - Breustedt, B.; Blanchardon, E.; Castellani, C-M.; Etherington, G.; Franck, D.; Giussani, A.; Hofmann, W.; Lebacq, A-L.; Li, W.B.; Noßke, D.; Lopez, M.A.
European Radiation Dosimetry Group (EURADOS) Working Group 7 is a network on internal dosimetry that brings together researchers from more than 60 institutions in 21 countries. The work of the group is organised into task groups that focus on different aspects, such as development and implementation of biokinetic models (e.g. for diethylenetriamine penta-acetic acid decorporation therapy), individual monitoring and the dose assessment process, Monte Carlo simulations for internal dosimetry, uncertainties in internal dosimetry, and internal microdosimetry. Several intercomparison exercises and training courses have been organised. The IDEAS guidelines, which describe – based on the International Commission on Radiological Protection's (ICRP) biokinetic models and dose coefficients – a structured approach to the assessment of internal doses from monitoring data, are maintained and updated by the group. In addition, Technical Recommendations for Monitoring Individuals for Occupational Intakes of Radionuclides have been elaborated on behalf of the European Commission, DG-ENER (TECHREC Project, 2014–2016, coordinated by EURADOS). Quality assurance of the ICRP biokinetic models by calculation of retention and excretion functions for different scenarios has been performed and feedback was provided to ICRP. An uncertainty study of the recent caesium biokinetic model quantified the overall uncertainties, and identified the sensitive parameters of the model. A report with guidance on the application of ICRP biokinetic models and dose coefficients is being drafted at present. These and other examples of the group's activities, which complement the work of ICRP, are presented.